Lokakarya Badan Layanan Umum Daerah Sebagai Kegiatan Pengabdian untuk Kemandirian Organisasi - Saiful Amri; Syamsul Rizal; Saiful; Sarboini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This service activity aims to improve the management of the Regional Public Service Unit (BLUD) in Aceh Jaya through a series of workshops, training, and cooperation between various stakeholders. The approach to implementing activities includes identifying critical issues, developing improvement strategies, testing strategies, and improving transparency and financial management. This activity involved local authorities, BLUD staff, local communities, and advocacy groups. The outcomes of this activity include increased financial transparency, increased BLUD employee capacity, tested successful innovation strategies, improved collaboration, increased organizational independence, and perceived benefits. community benefit. This activity also involved teams from Akademi Keuangan Perbankan Nusantara, Universitas Serambi Mekkah, and Universitas Syiah Kuala. Overall, this service has had a positive impact on the management of BLUD in Aceh Jaya, increasing the organization's transparency, efficiency, and independence, and providing better benefits to the community.